Estimation of Sources and Marine Debris Dynamics Movement along the Coast of Sukajaya Lempasing Village, Lampung Province - Muhamad Gilang Arindra Putra; Kattia Setiyani Widiastuti; Yudo Pramono; Delilla Suhanda (Journal of Marine and Coastal Science, 2025)
The coastal zone is a transitional area characterized by complex dynamics influenced by the interaction between land and sea. One of the consequences of this interaction is the accumulation of solid pollutants in the form of waste, which has the potential to disrupt the surrounding ecosystem's balance. This study aims to estimate the origin and movement pathways of marine debris along the coast of Sukajaya Lempasing Village by analyzing surface current patterns. The methods applied include purposive sampling and both quantitative and qualitative descriptive analysis. Waste data collection followed the guidelines issued by the Ministry of Marine Affairs and Fisheries in 2024, while surface current simulations were conducted using MIKE 21 with the Flow Model Flexible Mesh module. Monitoring results indicated that plastic waste dominated at all stations, with the highest number recorded at Station 1 (671 items), which also had the greatest total waste weight, amounting to 38.5 kg. The average waste density in the study area was 4.82 pcs/m². Surface current speeds ranged from 0.004 to 0.008 m/s on March 28, 2024, and from 0.005 to 0.015 m/s on April 2, 2024. Based on modeling results and interviews with local residents, the primary source of the waste was river discharge, which was then transported by longshore currents and subsequently accumulated along the coast of Sukajaya Lempasing Village.